Characteristic of pore structure and cells growth on the various ratio of silk fibroin and hydroxyapatite in Chitosan base scaffold - Thunsiri K. (2017)
© 2016 Trans Tech Publications, Switzerland. In this study, Chitosan (CS), Silk Fibroin (SF), and Hydroxyapatite (HA) were selected for scaffold fabrication. The scaffolds were fabricated by freeze drying technique to produce a porous structure. Silk cocoons and bovine bone were used to synthesize the SF and HA, respectively. While CS was produced from commercialized product made from squid pen. The CS was selected as a main structure of the scaffold which was fixed at 50% by weight ratio of the specimen. Another fifty percent are the various ratio of HA and SF. The result confirmed the extraction of silk cocoons and bovine bones were acceptable used as HA and SF. The HA and SF ratio that provided the highest porosity percentage was 25:25, while the highest percentage of cells growth in 7 and 21 days was 50:0 ratio. According to MTT-assay results, the scaffolds in every ratio could be used as a tissue engineering structure for cell proliferation as well as cartilage repairing in the future.